IoT based Child Protection Using Android App - N. , Senthamilarasi; S. , Shruthi; S.B. , Sushma; S. , Swethalakshmi (International Journal of Psychosocial Rehabilitation, 2020)
The sad and horrifying truth about today’s society is that children are not safe in any part of the world. Studies show that about 5 to 6 million kids are subjected to maltreatment every year. The proposed system is basically to design a smart child safety wearable device that goes unnoticed by the public. An Android application will track all the activities through the device and report to the parents. It includes sensors like temperature, pulse rate, and heartbeat that will monitor the child 24/7. A gas sensor is added to detect the presence of alcohol or any sedatives present. It includes a GPS location system and sound amplification technique that helps the child during emergency situations. Along with all these components, there is a camera module that shows what kind of danger is awaiting the child. All this information will be sent to the server and viewed via the app whenever the values of the sensors exceed the threshold, along with snoozing of messages. In the absence of internet facilities, a GSM module is used to alert parents by SMS.